2016
DOI: 10.1002/jbm.a.35848
|View full text |Cite
|
Sign up to set email alerts
|

Surface chemistry regulates the sensitivity and tolerability of osteoblasts to various magnitudes of fluid shear stress

Abstract: Scaffolds provide a physical support for osteoblasts and act as the medium to transfer mechanical stimuli to cells. To verify our hypothesis that the surface chemistry of scaffolds regulates the perception of cells to mechanical stimuli, the sensitivity and tolerability of osteoblasts to fluid shear stress (FSS) of various magnitudes (5, 12, 20 dynes/cm ) were investigated on various surface chemistries (-OH, -CH , -NH ), and their follow-up effects on cell proliferation and differentiation were examined as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…Shear stress stimulates the release of factors such as nitric oxide (NO) and prostaglandins (e.g., PGE 2 ) by bone-derived cells and organ cultures (Johnson et al 1996; McAllister & Frangos 1999; Zaman et al 1999; McAllister et al 2000). For example, under 12 dynes/cm 2 shear stress, the release of adenosine triphosphate (ATP), NO and PGE 2 from rat primary osteoblasts was significantly higher vs. static control conditions (Li et al 2016). These factors can modulate bone cellular activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shear stress stimulates the release of factors such as nitric oxide (NO) and prostaglandins (e.g., PGE 2 ) by bone-derived cells and organ cultures (Johnson et al 1996; McAllister & Frangos 1999; Zaman et al 1999; McAllister et al 2000). For example, under 12 dynes/cm 2 shear stress, the release of adenosine triphosphate (ATP), NO and PGE 2 from rat primary osteoblasts was significantly higher vs. static control conditions (Li et al 2016). These factors can modulate bone cellular activity.…”
Section: Introductionmentioning
confidence: 99%
“…We now know bone cells release a myriad of factors that modulate blood vessel function (Alam et al 1992; Delany & Canalis 1997; Ishida et al 2002; Brandi & Collin-Osdoby 2006; Li et al 2016). What is not greatly appreciated is the reciprocal relation whereby bone blood vessels release factors (e.g., insulin-like growth factor-1, endothelin-1, prostacyclin, RANKL, interleukin-11, PGE 2 , NO, ATP, ADP, AMP, adenosine, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Because cells depend on specific proteins for anchorage and extracellular cues, the composition and conformation of adsorbed proteins at the material surface are key mediators of cell behavior (Bouet, Marchat, et al, ; Fourel et al, ; Streuli, ; Wilson, Clegg, Leavesley, & Pearcy, ). Material intrinsic properties and particularly surface properties (e.g., surface chemical functional groups) affect the key early event of protein adsorption and subsequent cell adhesion, growth, and differentiation (Anselme, Ponche, & Bigerelle, ; Bouet, Marchat, et al, ; Vitte, Benoliel, Pierres, & Bongrand, ), as well as their response to shear stress (Li, Luo, Huang, et al, , Li, Luo, Xie, et al, ; Li et al, ). Regarding shear stress responses, Li et al () demonstrated in 2D systems that the chemical functionalization of glass slides with terminal ‐OH, ‐CH 3 , and ‐NH 2 groups regulates primary rat osteoblast responses to fluid shear stress.…”
Section: Obstacles In Defining Optimal Flow Effectsmentioning
confidence: 99%
“…Beyond altered flow profiles (cf. Section 2), different levels of architecture defined by the manufacturing process significantly affect cell behavior (Li, Wang, Xing, Wang, & Luo, 2016;Marchat & Champion, 2017;Saiz, Zimmermann, Lee, Wegst, & Tomsia, 2013).…”
Section: Scaffold Architectural Features and Biological Responsementioning
confidence: 99%
See 1 more Smart Citation